Legal Protection for Land Rights Holders Beyond Administrative Registration: Re-Examining The Declarative Function of Land Registration in Indonesia - M. Filusi Ardiansyah; Darwati (Greenation International Journal of Law and Social Sciences, 2025)
Land registration has long been positioned as a central mechanism for achieving legal certainty within land administration systems. In Indonesia, registration is formally designed to function as a declarative mechanism that records and publicizes existing land rights, thereby supporting administrative order and evidentiary clarity. Nevertheless, in legal practice, land registration is increasingly treated as a decisive factor that determines the existence and enforceability of land rights. This shift reflects a tendency to equate legal protection with administrative registration status, rather than with the substantive legitimacy of land relations. This article examines legal protection for land rights holders beyond administrative registration by re-examining the declarative function of land registration in Indonesia. Using a normative juridical research method, the study analyzes statutory regulations, legal doctrines, and judicial reasoning to assess how far registration has departed from its intended evidentiary role. The analysis demonstrates that substantive land rights may arise independently of registration through possession, contractual relations, inheritance, and recognition under customary law. When registration is elevated to a quasi-constitutive status, these rights risk marginalization despite their legal legitimacy. The article argues that effective legal protection requires a clear distinction between the existence of land rights and the administrative mechanisms used to evidence them. Land registration should operate as a supportive instrument that strengthens legal certainty without excluding substantively valid rights. By reaffirming the declarative function of registration, Indonesia’s land administration system can better harmonize administrative certainty with substantive justice and ensure more inclusive protection for land rights holders.